THE ADMINISTRATION OF EMPLOYMENT IN SLOVAKIA (Cadernos de Dereito Actual, 2016)
The main objective of this article is to describe basics of administration of the employment in Slovak Republic. The intended outcome is to find out, using what authorities, what instruments and in what way the state tries to accomplish that as many individuals as possible have the job. The article is divided into three chapters. In the first chapter we define the concept of the administration of the employment in general. The content of the second chapter consists of description, which authorities operates in the sector of the employment, what objectives they have and what is their activity. Third chapter focuses on characteristic of providing employment services.